Development of autonomic innervation at the venous pole of the heart: bridging the gap from mice to human - Fleur Zwanenburg; Thomas A. Bos; Arend D. J. Ten Harkel; Monique C. Haak; Nathan D. Hahurij; Robert E. Poelmann; Conny J. van Munsteren; Lambertus J. Wisse; Nico A. Blom; Marco C. DeRuiter; Monique R. M. Jongbloed (Journal of Translational Medicine)
Abstract Background Prenatal development of autonomic innervation of sinus venosus-related structures might be related to atrial arrhythmias later in life. Most of the pioneering studies providing embryological background are conducted in animal models. To date, a detailed comparison with the human cardiac autonomic nervous system (cANS) is lacking. The aim of this study was to compare the morphological and functional development of the cANS between mouse and human, specifically aimed at the venous pole. Methods Wildtype mouse embryos (E9.5–E18.5) and healthy human fetuses (6–38 weeks gestational age (WGA)) were studied at sequential stages to obtain a comparative developmental series. Cardiac autonomic function was assessed through heart rate variability (HRV) analysis using ultrasound. Morphological assessment of the venous pole was performed using immunohistochemical stainings for neural crest cells and autonomic nerve markers. Results Murine cANS function did not definitively establish in utero as HRV parameters depicted no trend prior to birth. In contrast, human HRV parameters greatly increased from 20 to 30 WGA, indicating that human cANS function is established prenatally around 20 WGA and matures thereafter. Morphologically, cANS development followed a similar sequence with neural crest-derived nerves entering the venous pole in proximity to the developing pulmonary vein in both species. However, the timing of differentiation into sympathetic or parasympathetic phenotype was markedly distinct, as human autonomic markers emerged relatively later when related to major cardiogenesis. Structures related to arrhythmogenicity in humans, such as the ligament/vein of Marshall and the myocardium surrounding the pulmonary veins, become highly innervated during embryonic development in both mice and humans. Conclusion Although early morphological cANS development at sinus venosus-related structures follows a similar sequence in mice and humans, there are substantial differences in the timing of functional establishment and differentiation in sympathetic and parasympathetic phenotypes, which should be taken into account when extrapolating mouse studies of the cANS to humans. The abundant innervation of sinus venosus-related structures may play a modulatory role in arrhythmogenesis under pathological conditions.